Socio-Economic Factors of Poverty in Rural Areas of Almaty Region and Prospects for their Regulation - R. A. Kuzembekova; A. N. Zhanbyrbayeva (Экономика: стратегия и практика, 2022)
The article reveals the main factors influencing the dynamics of the severity and depth of poverty in rural areas of Almaty region, and proposals for ensuring employment and equalizing the incomes of the rural population. The introduction presents the goal of the research: analysis of the socio-economic factors of poverty in rural areas of the Almaty region and their regulation. Also presents the characteristics of the Almaty region and the relevance of the problem. The literature review provides an analysis of modern research on the problem of poverty in rural areas of the Almaty region, the latest scientific approaches to its solution in the context of urbanization, and changes in traditional business models. The methods and materials describe the characteristics of the research methodology based on the use of analysis, synthesis, anduniquel economic and socio-statistical methods. The application of economic and statistical analysis, method of relative evaluation is justified. The results of research reveal the analysis of the effectiveness and risks of development schemes for the Almaty region and the impact of factors such as urbanization, redistribution of budget financing schemes, internal migration processes on the depth and severity of poverty. The discussions substantiated the disproportions of the territories of the Almaty region and their risks of increasing the depth and severity of poverty. This requires a state policy to strengthen the transport, trade, and industrial infrastructure of rural areas. The conclusion describes recommendations, integration of depressed rural areas into the trade and production infrastructure and support of backbone enterprises.